Dakwah dan Komunikasi - Ismet Rum (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2015)
Preaching and communication are the two activities go hand in hand that can’t be separated from each other on the life of a preacher. Vehicle travels is “kalimatun tayyibah”, a kind word. And provision journey is “uswatun hasanah”, exemplary. The torch lighting the way is “fiqhus sira nabawiyah”, understand and appreciate the life history of the Prophet. And signs his journey is al-Qur an and Sunnah. Objectives and targets that trip was the pleasure of Allah SWT. So propaganda and communication positive, productive, innovative preachers heir of the Prophet, is the activity that characterizes social life, which is worth “rahmatan lil'alamin